LE PRONOM FRANÇAIS "ON" DANS LA POÉSIE DE IULIA HAŞDEU. COMPLEXITÉ RÉFÉRENTIELLE ET TRADUCTION - MATEIU, Iuliana-Anca (Studia Universitatis Babeș-Bolyai Philologia, 2022)
The French Pronoun ON in Iulia Haşdeu's Poetry. Referential Complexity and Translation. In our paper, we intend to explain the frequency of the French pronoun ON in the poetry of Iulia Haşdeu and the variety in translating its constructions into Romanian through a comparative stylistic analysis and an enunciative analysis of its occurrences and translations. Due to its indetermination, ON can be used in a lot of contexts, or it can be suppressed in those contexts where predication is more important than reference. Article history: Received 5 July 2022; Revised 31 October 2022; Accepted 15 November 2022; Available online 20 December 2022; Available print 30 December 2022. REZUMAT. Pronumele francez ON în poezia Iuliei Haşdeu. Complexitate referenţială şi traducere. În cadrul articolului, ne propunem să explicăm frecvenţa pronumelui francez ON în poezia Iuliei Haşdeu și varietatea traducerilor construcțiilor cu ON printr-o analiză stilistică comparativă și o analiză enunțiativă a ocurenţelor şi traducerilor sale. Datorită indeterminării, ON poate fi folosit într-o mulțime de contexte sau poate fi suprimat în contextele în care predicația contează mai mult decât referința. Cuvinte-cheie: On, complexitate referenţială, poezie, traducere, analiză enunţiativă